Impact of implementing a local nutritional strategy on the outcome of critically ill patients in our main hospital - Reham Hossam Mohamed Zaki; Amr Abdulla Elsayed; Ehab Mahmoud Elreweny; Tamer Nabil Habib (Alexandria Journal of Medicine)
Introduction Introducing proper nutrition interventions to critically ill patients has been proven effective in mitigating the metabolic stress response and positively influencing immune reactions. Providing nutritional support to critically ill patients helps prevent further metabolic decline and preserves lean body mass.Material and Methods This study was conducted in Critical Care Units 1, 2, 3 and 4 at our Main Hospital included 316 patients divided into 2 groups, 155 patient (control group) and 161 patient (interventional group), where the interventional group was subjected to local nutritional protocol; which is based on various existing guidelines, meta-analyses, and randomized controlled trials (RCTs). The comprehensive study focuses on the impact of the local nutritional protocol on length of ICU stay, length of hospital stay, survival at 30 days, and at 90 days.Results There is statistically significant difference between interventional group ICU stay and control group ICU stay with P-value <0.001. Also, there is statistically significant difference between interventional group hospital stay and control group hospital stay with P-value <0.001. For 30 days overall survival; mean survival time of interventional group compared to mean survival time of control group, results show statistically significant with P-value <0.001. For 90 days overall survival; mean survival time of interventional group compared to mean survival time of control group results show statistically significant with P-value <0.001.Conclusions Applying our local nutritional protocol effectively reduced the duration of ICU stay, duration of hospital stay, 30 days all-cause mortality rate and mortality rate at 90 days.